Printed titanium implants in UK craniomaxillofacial surgery. Part I: access to digital planning and perceived scope for use in common procedures. Issue 3 (April 2021) - Goodson, A.M.C.; Parmar, S.; Ganesh, S.; Zakai, D.; Shafi, A.; Wicks, C.; O'Connor, R.; Yeung, E.; Khalid, F.; Tahim, A.; Gowrishankar, S.; Hills, A.; et al.
Abstract: This first part of a two-part study examines perceived applications for and barriers to using printed titanium in light of current caseloads, funding pathways, and use of digital planning. It aims to demonstrate the scope for printed titanium in modern practice and to guide industry about the needs of UK surgeons. A cross-sectional study over 14 weeks was performed electronically with support from the British Association of Oral and Maxillofacial Surgeons (BAOMS) and a national trainee-led recruitment team. Ethics approval was obtained at the lead centre. A total of 132 participants joined the study (70% consultants, 25% specialty registrars, and 5% other), approximating a 29% response rate from consultant/registrar BAOMS members throughout mainland UK. Eighty-eight per cent used CAD-CAM design, with highly variable funding/access, design/manufacturing workflows (in-house/outsourced). Eighty-eight per cent were involved with trauma, 61% with orthognathic, and 52% with oncology-reconstruction surgery. Favourite applications for printed titanium were orbital floor repair (89%) and free-flap jaw reconstruction (87%). Most participants also cited maxillary/zygomatic osteotomies and cranioplasty (range 61%-73%). Although a popular application (78%), the evidence base in temporomandibular joint surgery is limited. Those performing orthognathic surgery perceived more indications than those who did not (p=0.013). Key barriers included cost, turnaround time and logistics, and the need to be trained in traditional techniques. Printed titanium was useful for both common and niche procedures, but was specifically limited in emergency trauma. Most surgeons had experience in CAD-CAM surgery but technical understanding appeared unclear. Limiting factors included variable funding and production pathways, perceived costs, and logistics, but in-house design can minimise them. In part II, we quantify perceived benefits and limitations and whether surgeons' understanding and knowledge are sufficient to rationalise them.